ROC Curve Analysis of the Sensitivity and Specificity of Biochemical Detection of Intrahepatic Cholestasis during Pregnancy - Huang, Xiaoyi; Chen, Siyi; Chen, Hongyan; Hu, Liang; Wen, Lijuan; Wei, Fengxiang; Chen, Ken (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Introduction Intrahepatic cholestasis of pregnancy (ICP) is associated with an increased risk of adverse pregnancy outcomes in mothers and infants. The aim was to evaluate the sensitivity and specificity of biochemical detection of ICP by ROC curve and to determine the threshold of more reliable experimental indicators.Materials and Methods 305 patients and 305 healthy pregnant women were enrolled in the study.Results The average levels of TBA, ALT, and AST in the ICP group were much higher than those in the control group (P<0. 001); the area of both CG and TBA under ROC curve was up to 0.99, the sensitivity was 97.7%, and the specificity was 99.3%.Conclusions This study did not find any single specificity and sensitivity markers that could be used to reliably diagnose ICP. In the future, we will pay more attention to the correlation between sensitive biochemical indicators and adverse pregnancy outcomes.
Keywords: intrahepatic cholestasis of pregnancy; diagnostics; roc curve